Diálise peritoneal : experiência de dez anos de um centro de referência no nordeste do Brasil - Moura, Alvimar Rodrigues de (2017)
We accessed data on patients undergone peritoneal dialysis (PD), a technique that is underused in most countries and is not usually employed as the initial therapeutic option. The study aimed to characterize the DP program at a reference unit in the Northeast Region of Brazil. It was based on a retrospective cohort study that evaluated the clinical and socio-demographic profile, treatment history and causes of death of 565 incident patients who remained in PD for at least 30 days. Results were obtained: mean age was 54 ± 19 years when they started on PD. Males were 55%, 38% from Aracaju, 62% from Sergipe, 76% had <4 years of schooling and 88% earned <5 minimum wages as family income. Diabetic nephropathy was the main etiology (25%) and 77% were hypertensive. There was 9% of late referencing. The majority started on PD as the first dialytic procedure (53%), and (58%) as an emergency. The patients remained in PD for an average of 710.5 (± 714.2) days. PD was the initial dialysis modality for 302 patients (53%). A total of 676 peritoneal catheters were implanted, mean of 1.19 / patient. The median survival of the PD technique was 83.1 months, with a rate of 85.1% in 2 years and 61.1% in 5 years. The median survival of patients was 32.9 months for patients without DM, with a 2-year survival rate of 52.4% and a 5-year survival rate of 22.3. During the study, 353 individuals (62%) died. The etiology of renal disease was identified in 37% of the cases. The odds ratio (OR) of death of those who were referred late was 2,032 times greater than those who did conservative treatment. In conclusion, despite non favorable social indices, survival, peritonitis and complications rates were similar to those described in the literature.